Phenolic profile of wild fruits of Rosa canina SL. from Northeast Portugal - Guimarães, Rafaela (2013)
Plant polyphenols are a wide group of secondary metabolites and are a common component of our diet. Flavonoids represent the most common and widely distributed group of plant phenolics, and can be further broken into classes including flavones, flavonols, flavanones, flavanols, anthocyanins and isoflavonoids. Different classes of bioactive constituents are present in Rosa canina, including phenolic compounds. Rosa canina fruits can be eaten raw as snacks and possess prophylactic and therapeutic activities against a wide range of ailments, including the inflammatory disorders arthritis, rheumatism, gout, colds and gastrointestinal disorders, which might be related with their phenolic composition. This study aimed to characterize the phenolic compounds present in the above mentioned wild fruits. The analysis of phenolic compounds was carried out by reversed-phase HPLC-DAD and the major phenolic compounds were identified by ESI-MS, in order to establish the specific phenolic profile. Rosa canina presented different classes of flavonoids. Flavones, flavonols and dihydroflavonols represented 5.50 mg/100 g dry weight, among which taxifolin, a dihydroflavonol, was prominent (1.18 mg/100 g). Flavan-3-ols (i.e., catechins and proanthocyanidins) were other relevant flavonoids found. (+)-Catechin was the most abundant flavan-3-ol found in the fruits (3.59 mg/100 g), whereas cyanidin 3-O-glucoside was the only anthocyanin detected (0.68 μg/100 g). The studied fruits may have great potential for food industries as a source of colors and flavors, as well as bioactive molecules such as phenolic compounds for dietary supplements or functional foods.